CONTRIBUTION OF THE MEDIA IN THE FIGHT AGAINST CLIMATE CHANGE IN DRC. STUDY CONDUCTED AT RTNC/KISANGANI - SENGI, Symphorien BAMBISINGO; AMATCHO, Daddy ALIFI; ASIMWE, Lydie MAKURU (IJRDO-Journal of Applied Science, 2021)
In recent decades, the issue of the environment has become more and more pressing about the threat that the planetary space is experiencing in its ecosystem, particularly with climate change. A concept that to this day shines on everyone’s lips, because of its dangerousness, that of bullying all of nature through its elements, in this case the pollution that emanates from industrialized countries. As a result, the fight against climate change becomes undeniable since it presents disadvantages in the functioning of the environment. A debate that the media must embrace to sensitize populations on the harmful effects of climate change. Unfortunately for our media, the question is not of the day, disinterestedness can be seen in the programming policy of the grid, in particular the RTNC/Kisangani to sensitize the population for this cause. A problem that we formulated our question on the why of this disinterestedness which constitutes the keystone of this article. In view of the above, we have in this research selected a sample which is our study environment, the RTNC / Kisangani to understand this lack of interest in the context of processing information and the animation of related programs. With the fight against climate change in the city of Kisangani. And we understood that at the end of this research that 77% of the respondents confirmed that there is no real change in the behavior of the population regardless of the programs programmed for this purpose due to the lack of journalists at the RTNC / Kisangani able to deal well with this issue of the fight against climate change, especially knowledge in this area. This research, apart from the introduction and the conclusion includes three points, the first of which looks at terminological lighting where the emphasis is on the nation of media and the notion of climate change with its related concepts, the second is focused on the general concept of the study and the last deals with the results.